IbM Kelompok Usaha Kecil Produksi Pupuk Cair Organik "Media Subur Wijaya" di Kecamatan Srengat Kabupaten Blitar - Tjahjo Purtomo; Siti Mujanah; Gatot Sargiman (JPM17: Jurnal Pengabdian Masyarakat, 2014)
Abstract.Â It is estimated that the plantation sub-sector fertilizer needs for 2010 through 2025 for urea, Superphos and KCl decreased. Instead NPK compound fertilizer demand is increasing. This is because the single fertilizer NPK fertilizer has been converted into a proportional basis. The use of organic fertilizer prioritized for seasonal crops (sugar cane, cotton, tobacco, patchouli, lemon grass, roots, fragrant and serehwangi) and for annual crops (coffee and cocoa). One of the producers of fertilizer that can be expected as a supplier of fertilizer demand in Indonesia is "Fertile Media Wijaya" (MSW). Their products in the form of liquid organic fertilizer that has proved useful in several times damplot test for rice, soybeans, corn, onions, potatoes and coconut oil. Liquid fertilizer is produced in the Desa Pakisrejo, Kecamatan Srengat Blitar and Desa Gondang Kecamatan Purwodadi since 2009. The process of making the MSW organic liquid fertilizer is traditionally done manually and by using small drums each with a capacity of 70 liters, so it requires a lot of places and can not accept orders in large amounts continuously. Time manufacturing process takes Â± 60 days. IBM is expected to resolve the constraints that occur, and the process can increase production and marketing of liquid organic fertilizer smoothly.Keywords: MSW Organic Liquid Fertilizer